Pengaruh Penggunaan Kredit Usaha Rakyat Terhadap Pendapatan UMKM (Studi Kasus Umkm Komplek MMTC Medan) - Hutagalung, Daniela; Siahaan, Audrey M.; Hutapea, Herti Diana (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of the use of People's Business Credit (KUR) on the income of Micro, Small, and Medium Enterprises (MSMEs) in the MMTC Complex in Medan City. MSMEs have a strategic role in driving economic growth, but still face capital constraints. KUR, as a government-subsidized financing program, is expected to help overcome these constraints. The research method used is quantitative with a survey approach. Primary data was obtained through questionnaires distributed to 32 MSME respondents in the MMTC Complex in Medan who had received KUR facilities. Data analysis used a simple regression test to determine the relationship between the KUR variable and MSME income. The results showed that KUR had a positive and significant effect on MSME income. This is indicated by the t-count value of 9.951 which is greater than the t-table of 1.66088, and a significance value of 0.000. The coefficient of determination (R²) shows that 76% of the variation in MSME income is influenced by KUR, while the rest is influenced by other factors outside the study.